2 Del. Laws 1136-37 (1797) - (:unkn) unknown (My University, 1793)
Chapter 36-An Act for Establishing the Militia in this State, § 4: Required all citizens enrolled in the militia to arm themselves, within six months, with a good musket or firelock, a bayonet, belt, two spare flints, a knapsack, a pouch, and a box to contain not less than twenty-four cartridges and gunpowder suited to the bore of his gun, or twenty cartridges and a quarter-pound of gunpowder.
Keywords: REQUIRED POSSESSION